1999
DOI: 10.1007/s11661-999-0230-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Ti and TiO2 additions on the pressureless sintering of B4C

Abstract: The effect of TiO 2 and of Ti additions on the sintering behavior of B 4 C was studied in the 1800 ЊC to 2190 ЊC temperature range. According to thermodynamic predictions that were verified by the experimental results, TiB 2 is formed in situ in both instances. Titanium oxide is reduced by carbon that originates in B 4 C and decreases its carbon content. The activity of carbon in the boron carbide phase is reduced significantly with decreasing carbon content. By sintering at 2160 ЊC for 1 hour, a mixture of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
74
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 14 publications
2
74
0
Order By: Relevance
“…In a previous communication we have reported on the microstructure of B 4 C-TiB 2 composites in which a very strong interface prevails between the two ceramic phases [4,11], and on B 4 C-CrB 2 composites, in which considerable pull-out of CrB 2 particles had been detected [12]. These behavior patterns correlate with the thermal residual stresses in the composites, generated by the differences of thermal expansion coefficients (α) of B 4 C and the boride phases.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In a previous communication we have reported on the microstructure of B 4 C-TiB 2 composites in which a very strong interface prevails between the two ceramic phases [4,11], and on B 4 C-CrB 2 composites, in which considerable pull-out of CrB 2 particles had been detected [12]. These behavior patterns correlate with the thermal residual stresses in the composites, generated by the differences of thermal expansion coefficients (α) of B 4 C and the boride phases.…”
Section: Resultsmentioning
confidence: 96%
“…Grain boundary and volume diffusion that control the densification rate become effective only above 2000°C because of the high fraction of covalent bonds (>90%) in the carbide phase [2]. Various additives have been used in order to decrease the sintering temperature [1, [3][4][5][6][7]; a relatively low-porosity fraction (1-5 vol.%) can be attained only by sintering above the 2150-2200°C temperature range. We have previously reported that the addition of Fe to low-cost boron carbide powder allows fabricating boron carbide bodies with 6-8 vol.% porosity at 2100 °C, while pure powder at the same temperature allows attaining a relative density of about 70% [8].…”
Section: Introductionmentioning
confidence: 99%
“…The sinterability of B 4 CTiO 2 mixtures was confirmed by Levin et al, who fired B 4 C-TiO 2 Powder compacts and obtained B 4 C-TiB 2 composites as did Kristics groups [19]. However, practically useful levels of densification (more than 90% of the TD) could be attained only at temperature of 2,200 -C; considerably higher than that indicated by Kristic and coworkers.…”
Section: Introductionmentioning
confidence: 76%
“…Since alkoxides of transition metals are highly reactive towards water, TTIP precursor can readily reacts with water via the following reaction to form titanium hydroxide 12 .…”
Section: Resultsmentioning
confidence: 99%